Axial load-capacity of rectangular cement stabilized rammed earth column. (15th September 2015) - Tripura, Deb Dulal; Singh, Konjengbam Darunkumar
Highlights: Lateral and vertical deflection. Experimental value and the value predicted by tangent modulus theory tend to converge. Load carrying capacity increases with the increase in aspect ratio. Codal predictions of stress reduction factors are un-conservative with respect to experimental findings. Characteristic strength of CSRE column yields relatively higher factor of safety. Abstract: The paper presents a novel study on structural behaviour of axially loaded cement stabilized rammed earth (CSRE) prisms and columns of square and rectangular cross-sections. The effects of slenderness ratio and aspect ratio on the load-capacity of columns and stress reduction factors were assessed. Experimental results were compared with that obtained by tangent modulus theory. Experimental capacity/stress reduction factors were compared with published codal values. The result shows that the load-capacity of column decreases as the value of slenderness ratio increases and aspect ratio of column was found to influence the load-capacity. The ultimate compressive strength of column predicted by tangent modulus theory tend to converge the experimental values at higher slenderness ratios. The stress reduction factors in earthen (NZS 4297, AS HB 195) and masonry (IS 1905) standards are found to be in close agreement with the experimental values. The characteristic strength of column yields relatively higher safety factor (∼23–35) indicating a possibility of using CSRE for construction of load-bearing houses.